Influence of Occlusal Splint on Mandibular Movements in Patients with Bruxism: a Comparative Pilot Study - Josip Škaričić; Samir Čimić; Sonja Kraljević-Šimunković; Marko Vuletić; Nikša Dulčić (University of Zagreb. School of Dental Medicine, 2020)
Objective: The objective of this pilot study was to examine the impact of occlusal splint treatment on mandibular border movements and the condyle position in subjects with bruxism. Material and methods: The study included 9 subjects diagnosed with bruxism (mean age 28.7) and 9 subjects in the control group (mean age 30.5). All subjects were adults, eugnathic, and with a dentoalveolar Angle Class I, without prosthetic restorations, previous or current orthodontic treatments, a systemic disease or previous surgical interventions in the temporomandibular joint. All experimental and con-trol group subjects were provided with a standardized relaxation occlusal splint, which they wore for 8 weeks. During this time, an initial and three additional measurements of incisal opening (IO), left condyle opening (OLC), right condyle opening (ORC), left laterotrusion (LLI) and right laterotrusion (LRI) (after 2, 4 and 8 weeks) were performed using an Arcus Digamma II (Kavo) ultrasound device for mandibular movements recording. Using the same instrument, the condylar position during protrusion, left and right laterotrusion, and in the centric relation position (CR) was analyzed initially and after 8 weeks using the maximum intercuspation as reference point. Continuous variables were described using basic statistical parameters, and the statistical significance of differences between the variables was checked by the t-test and χ2 test (p <0.05).Results: The values of IO, OLC, ORC, LLI and LRI increased after 8 weeks of wearing, with the highest increase for OLC, by 13.8%. No statistically significant difference (p <0.05) was found for any changes in movements. Changes in the condyle position during all movements and those in the CR were higher in the experimental group for 10 out of 14 measured parameters compared to the control group. A statistically significant difference was established for 5 out of 14 measured parameters after the occlusal splint treatment. Conclusions: The results of this pilot study have proven the influence of the occlusal splint treatment on mandibular border movements in subjects with bruxism by increasing the range of movements. Also the changes of the condyle position in subjects with bruxism were greater compared to those in healthy subjects.